Sulfur Loading as a Manufacturing Key Factor of Additive-Free Cathodes for Lithium-Sulfur Batteries Prepared by Composite Electroforming - Wassima El Mofid; Timo Sörgel (Energies, 2023)
The promised prospects of Li–S technology, especially within the energy situation of the 21st century, have sparked a renewed interest from the scientific community in the 2000s. In this context, we present our new vision for the fabrication of novel cathodes for Li–S batteries that were synthesized using the first combination of composite plating and electroforming (composite electroforming). The latter consists of electroforming the current collector foil directly in a one-step process. Simultaneously, the active material is introduced into the metal matrix by means of composite plating. Reduced technological steps, better performance and resource-saving production, combined with a potentially easier and highly efficient way of recycling electrodes, are achievements of the current method. In the present work, novel cathodes for lithium–sulfur batteries were synthesized by composite electroforming of AlSi10Mg0.4@Ni foil from a nickel sulfamate-based electrolyte with AlSi10Mg0.4 particles used as dispersoids. The composite foil is subsequently etched in order to increase the specific surface area of the aluminum alloy particles. The last manufacturing and key step of the ready-to-use cathodes for Li–S batteries is the sulfur loading, which was conducted using two different ways: by spin coating in melted sulfur at 160 °C or electrochemically from a sodium sulfide aqueous solution (Na2S(aq)). Morphological and electrochemical characterization by SEM and galvanostatic cycling, respectively, exhibited a remarkable difference in terms of the sulfur distribution and the surface morphology as well as a considerable improvement of the rate capability and cyclability for the electrochemically loaded cathode as against the spin-coated one.